Correct Answer:
a = -3/2, b = 13/4
if a + i is a root of the equation x2 + 3x + b = 0 then it should satisfy the equation.
that is (a + i)2 + 3(a + i) + b = 0
after simplifying we will get
a2 + i2 +2ai + 3a + 3i + b = 0
we know that i2 = -1
therefore, a2 - 1 +2ai + 3a + 3i + b = 0
we can write it as
a2 - 1 + 3a + b +2ai + 3i = 0
or a2 - 1 + 3a + b +(2a + 3)i = 0
by equating real and imaginary parts to 0, we will get
a2 - 1 + 3a + b = 0 and 2a + 3 = 0
2a + 3 = 0 gives a = -3/2
substitute the value of a into a2 - 1 + 3a + b =0 , and we get
9/4 - 1 - 9/2 + b = 0
therefore
9/4 - 4/4 - 18/4 + b = 0
-13/4 + b = 0
-13/4 = -b
which gives b = 13/4
answer: a = -3/2, b = 13/4
|